Effectiveness of Mango Leaf Extract (Mangifera indica L) on Healing of Second Level Cut Wound in Male White Mice (Mus musculus) - Suhatri, Suhatri; Fidiyani, Dwi; Azzahra, Nia; Suardi, Muslim (JURNAL KESEHATAN TERAPAN, 2022)
Mango leaves have several secondary metabolites which have pharmacological effects and may be used to cure cuts or other injuries. The purpose of this study was to determine the effectiveness of the mango leaf extract on wound healing in male white mice. This experimental research was carried out at the Pharmacy Laboratory, Universitas Kader Bangsa and STIK Siti Khodijah, Palembang in July to August 2021. Mango leaves were macerated using 96% ethanol. The extract obtained was prepared into the ointment at concentrations of 10, 20, and 40%. Mango leaf extract ointment, positive, and negative control were each applied twice daily. Wound length was measured using a caliper on days of 2, 4, 6, 8. 10, 12, and 14. The percentage reduction in wound length on day 14 after administration of mango leaf extract ointment 10, 20, and 40% were 14,4±2.07; 17.2±3.70 and 16.4±4.15%; respectively. While the positive control and negative control were 25.4±3.05 and 11.4±1.14%, respectively. There was a significant difference between the administration of the mango leaf extract ointment at concentrations of 20 and 40% compared to the negative control (p<0.05). The mango leaf extract is quite effective in healing Level II cut wounds. Keywords: Bioplacenton, mango leaf extract, wound.